Alkyl gallates inhibit serine O-acetyltransferase in bacteria and enhance susceptibility of drug-resistant Gram-negative bacteria to antibiotics - Toyomoto, Touya; Ono, Katsuhiko; Shiba, Tomoo; Momitani, Kenta; Zhang, Tianli; Tsutsuki, Hiroyasu; Ishikawa, Takeshi; Hoso, Kanae; Hamada, Koma; Rahman, Azizur; Wen, Liping; Maeda, Yosuke; et al. (Frontiers in Microbiology, 2023)
A principal concept in developing antibacterial agents with selective toxicity is blocking metabolic pathways that are critical for bacterial growth but that mammalian cells lack. Serine Oacetyltransferase (CysE) is an enzyme in many bacteria that catalyzes the first step in L-cysteine biosynthesis by transferring an acetyl group from acetyl coenzyme A (acetyl-CoA) to L-serine to form O-acetylserine. Because mammalian cells lack this L-cysteine biosynthesis pathway, This is a provisional file, not the final typeset article developing an inhibitor of CysE has been thought to be a way to establish a new class of antibacterial agents. Here, we demonstrated that alkyl gallates such as octyl gallate (OGA) could act as potent CysE inhibitors in vitro and in bacteria. Mass spectrometry analyses indicated that OGA treatment markedly reduced intrabacterial levels of L-cysteine and its metabolites including glutathione and glutathione persulfide in Escherichia coli to a level similar to that found in E. coli lacking the cysE gene. Consistent with the reduction of those antioxidant molecules in bacteria, E. coli became vulnerable to hydrogen peroxide-mediated bacterial killing in the presence of OGA. More important, OGA treatment intensified susceptibilities of metallo-b-lactamase-expressing Gram-negative bacteria (E. coli and Klebsiella pneumoniae) to carbapenem. Structural analyses showed that alkyl gallate bound to the binding site for acetyl-CoA that limits access of acetyl-CoA to the active site. Our data thus suggest that CysE inhibitors may be used to treat infectious diseases caused by drug-resistant Gram-negative bacteria not only via direct antibacterial activity but also by enhancing therapeutic potentials of existing antibiotics.